Investigating the influence of culture on language patterns: a contrastive corpus-based study - Navarro, Sandra (TradTerm, 2021)
This paper aims to explore the intrinsic relationship between language and culture. It attempts to shed light on the underlying cultural associations embedded in collocational meaning across languages. The notion of culture adopted in this study is related to how individuals perceive the world and interpret reality around them. This paper brings together the principles of Corpus Linguistics and Intercultural Studies to investigate a corpus of travelers’ reviews (English/Portuguese) and interpret results within the framework of the model of cultural orientations in Walker et al. (2003). In a study of collocations with the word staff and their equivalents in Portuguese, we demonstrate how a language pattern can also represent a cultural pattern, thus showing that cultural orientations play a role in the identification of collocational meaning across languages.